The fermentation kitchen : recipes and techniques for kimchi, kombucha, kōji, and more - Cooper, Sam (Cook) (DK Publishing, 2024)
From kimchi to miso, kombucha to ginger beer, 'The Fermentation Kitchen' introduces you to the alchemy of fermentation - taking simple ingredients and transforming them in form and flavour. Explore a wide range of authentic and adapted techniques from across cultures and continents and harness bacteria, yeast, and fungus to create a variety of ferments to add flavour to dishes, boost gut health, and give perishable produce a new lease of life. Reconnect with these natural processes and learn to incorporate ferments into your everyday cooking with guides to flavour, texture and aroma alongside recipe ideas serving as inspiration.